Surgical Staging of Locally Advanced Cervical Cancer: Current Status and Research Progress - He Zhang; Weimin Kong; Shuning Chen; Xiaoling Zhao; Dan Luo; Yunkai Xie (Frontiers in Oncology, 2022)
Locally advanced cervical cancer (LACC) has large localized lesions, high recurrence and metastasis rate under standard treatment, and low survival rate. The current guidelines still use concurrent radiotherapy as the gold standard of treatment for locally advanced cervical cancer. Several recent studies have shown that surgical staging has higher accuracy in determining metastasis in the para-aortic lymph nodes, bringing survival benefits to some patients. However, the indications for surgical staging and whether surgical staging can improve prognosis are still controversial. We will review the current status and research progress of surgical staging for locally advanced cervical cancer.